2005
DOI: 10.1038/sj.bjp.0706407
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin induces hyperexcitability at motor and autonomic neuromuscular junctions through effects on voltage‐gated sodium channels

Abstract: 1 Oxaliplatin, an effective cytotoxic treatment in combination with 5-fluorouracil for colorectal cancer, is associated with sensory, motor and autonomic neurotoxicity. Motor symptoms include hyperexcitability while autonomic effects include urinary retention, but the cause of these side-effects is unknown. We examined the effects on motor nerve function in the mouse hemidiaphragm and on the autonomic system in the vas deferens. 2 In the mouse diaphragm, oxaliplatin (0.5 mM) induced multiple endplate potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 38 publications
4
81
0
2
Order By: Relevance
“…Patch-clamp technique studies performed on neurons isolated from the central nervous system of the cockroach showed that OXA was able to alter VGNaCs through a pathway involving calcium ions [13]. Taken together, these data are consistent with a channelopathy involving VGNaCs [11,12,13].…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Patch-clamp technique studies performed on neurons isolated from the central nervous system of the cockroach showed that OXA was able to alter VGNaCs through a pathway involving calcium ions [13]. Taken together, these data are consistent with a channelopathy involving VGNaCs [11,12,13].…”
Section: Introductionsupporting
confidence: 76%
“…The first is probably related to an axonopathy due to the accumulation of platinum compounds within the dorsal root ganglia, the second to a transient impairment of ion channel function, but there is still no agreement about which channel is involved [6][7][8][11][12][13], neither about the possible correlation between acute and chronic neurotoxocity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Oxaliplatin modifications of Na ϩ current include a slowing of inactivation kinetics (Adelsberger et al 2000;Wu et al 2009), reduction in current amplitude (Benoit et al 2006;Grolleau et al 2001;Wu et al 2009), and hyperpolarized shift in the voltage dependence of inactivation (Benoit et al 2006). Effects on Na ϩ channels have been suggested to alter axon excitability in patients treated with oxaliplatin (Kiernan and Krishnan 2006;Webster et al 2005). We considered the possibility that these direct effects of oxaliplatin might have produced results presented here because oxaliplatin can take many weeks to clear the blood (Levi et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Further, oxaliplatin administration has been described to slow sodium channel inactivation kinetics [1,34]. A change in sodium channel properties may predispose to ectopic activity, leading to paresthesia and fasciculations [36]. Cold exposure affects sodium channel kinetics [37] and, accordingly, sodium channel dysfunction is aggravated by cold temperatures [38].…”
Section: Introductionmentioning
confidence: 99%